Combination of Beetroot Juice, Honey and Green Apple on Hemoglobin Levels in Anemia Pregnant Women at Payung Sekaki Health Center, Pekanbaru - Septi Indah Permata Sari; Elly Susilawati; Shinta Devi; Berwi Fazri Pamudi (UIN Syarif Hidayatullah Jakarta, 2023)
Anemia is a medical condition characterized by lower-than-normal hemoglobin (Hb) levels. In pregnant women, anemia can lead to prolonged delivery times, increased bleeding, and shock during contractions. The adverse effects of anemia on the fetus include premature birth, low birth weight (LBW), potential disabilities, and infant mortality. The recommended solution to overcoming anemia in pregnant women is to consume a combination of beetroot juice and green apples juice. Beets contain essential components that can elevate Hb levels, whereas green apples provide minerals and vitamin C, enhancing iron absorption (Fe). This study aimed to investigate the effect of a combination of beetroot juice and green apple juice on Hb levels in pregnant women with anemia. The study population was comprised of 200 normal pregnant women, with a sample size of 15 in trimester III (TM III) with anemia, selected through purposive sampling. The intervention involved administering the juice daily for seven days. Data were collected using observation sheets and easy-to-touch devices. The research design was pre-experimental, utilizing a one-group pre-test–post-test design. This study was conducted within the working area of the Payung Sekaki Public Health Center (PHC) from January to April 2022. Dependent T-test analysis was used for data evaluation. The average Hb level of TM III pregnant women before juice consumption was 9.7 g/dL, which increased to 10.6 g/dL after the intervention. The dependent t-test results, with a 95% confidence level (Cl), indicated a p-value of 0.000, signifying a significant impact of fruit juice on the Hb levels of TM III pregnant women experiencing anemia. These findings suggest that clinical midwives should educate pregnant women about the importance of Fe tablets and the positive influence of fruit juice on Hb levels.